Individual analysis of EEG frequency and band power in mild Alzheimer's disease - Moretti, Davide V; Babiloni, Claudio; Binetti, Giuliano; Cassetta, Emanuele; Dal Forno, Gloria; Ferreric, Florinda; Ferri, Raffaele; Lanuzza, Bartolo; Miniussi, Carlo; Nobili, Flavio; Rodriguez, Guido; Salinari, Serenella; et al. (Clinical neurophysiology, 2004)
Objective: This EEG study investigates the role of the cholinergic system, cortico-cortical connections, and sub-cortical white matter on the relationship between individual EEG frequencies and their relative power bands. Methods: EEGs were recorded at rest in 30 normal elderly subjects (Nold), 60 mild Alzheimer disease (AD) and 20 vascular dementia (VaD) patients, comparable for Mini Mental State Evaluation scores (MMSE 17–24). Individual EEG frequencies were indexed by the theta/alpha transition frequency (TF) and by the individual alpha frequency (IAF) with power peak in the extended alpha range (5–14 Hz). Relative power was separately computed for delta, theta, alpha1, alpha2, and alpha3 bands, on the basis of the TF and IAF. Results: Using normal subjects as a reference, VaD patients showed ‘slowing’ of alpha frequency (TF-IAF) and lower alpha2 power; Mild AD patients showed lower alpha2 and alpha3 power; delta power was higher in both AD and VaD patients; Theta power was higher only in VaD patients. Conclusions: Individual analysis of the alpha frequency and power can discriminate mild AD from VaD and normal elderly subjects. Significance: This analysis may probe pathophysiological mechanisms causing AD and VaD.